A Creative Approach to Developing Students' Communication Skills - Ozodova Madina Khamzayevna (International Journal on Integrated Education, 2026)
This article discusses a creative approach to developing communication skills in primary school students, and presents suggestions and recommendations for improving the methodological aspects of developing students' communication skills in native language and reading literacy classes, and the integration of linguistic skills and the implementation of perceptual and semantic components of the reading process related to reading comprehension of literary and informational texts.